Treatment of falciparum malaria in Thai children - T. Chongsuphajaisiddhi (2018)
141 children with falciparum malaria admitted to the Hospital for Tropical Diseases in Bangkok were analysed. They were treated with one of the 5 regimes of antimalarials, and the dosage of each case was adjusted to the body surface area from the adult basic dosage: (i) Chloroquine 1500 mg base total over a period of 3 days; (ii) Sulfadoxine 1000 mg and pyrimethamine 50 mg (Fansidar 2 tablets) a single oral dose; (iii) Fansidar 2 tablets plus chloroquine 1500 mg base total over 3 days; (iv) Fansidar 2 tablets single oral dose plus quinine 500 mg base 8 hourly for 3 days; (v) Fansidar 2 tablets single oral dose plus quinine 500 mg base 8 hourly for 5 days. Of the 25 children treated with chloroquine, only one case (4.0%) showed radical cure while 11 cases (44.0%) showed RI failure, 7 cases (28.0%) RII, and 6 cases (24.0%) RIII. Out of 30 cases treated with a single dose of Fansidar, 23 cases (76.7%) were cured, while 5 cases (16.7%) showed RI failure and 2 cases (6.7%) RIII. From a total of 23 cases treated with Fansidar and chloroquine, 15 cases (65.2%) were cured, while 6 cases (26.1%) showed RI failure and 2 cases (8.7%) RII. Of the 31 cases treated with Fansidar and quinine, 21 cases (67.7%) were cured, while 9 cases (29.0%) showed RI failure and 1 case (3.2%) RII and of the 32 cases treated with a single dose Fansidar and quinine for 5 days, 29 (90.6%) were cured while 3 cases (9.4%) showed RI failure. The clinical and parasitological response in children with falciparum malaria to various antimalarials was discussed.